APAKAH METODE PEMBAYARAN PAYLATER AMAN? :SEBUAH INVESTIGASI DARI DIMENSI KEPERCAYAAN DAN KEAMANAN - Lestara Permana, Gusi Putu; Elsiani, Adek Ika (Universitas Prof.Hazairin,SH Bengkulu, 2022)
The fintech phenomenon in Indonesia continues to develop, one of the innovations is the service from an attractive fintech, namely pay later. Pay later which is a credit installment with a full digital service where the document submission is done online. This study aims to determine the trust and security in reusing the pay later feature on the marketplace. The object of this research is Pay later users who are located in Denpasar. The number of samples in this study was 50 respondents. The technique used is purposive sampling. The results showed that the variables of trust and security partially affect reuse. The trust variable has a positive and significant effect on the reuse of the pay later feature in the marketplace. Security has a positive and significant effect on reusing the pay later feature on the marketplace. The results of this study are expected to be useful for all Pay later users who use the Pay later feature as a reference in investigating the factors that influence the reuse of the Pay later feature.